2020
DOI: 10.1016/j.molcel.2020.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Implementation of Transgenic Microbes: Are We Ready for What Synthetic Biology Has to Offer?

Abstract: Synthetic biology has promised and delivered on an impressive array of applications based on genetically modified microorganisms. While novel biotechnology undoubtedly offers benefits, like all new technology, precautions should be considered during implementation to reduce the risk of both known and unknown adverse effects. To achieve containment of transgenic microorganisms, confidence to a near-scientific certainty that they cannot transfer their transgenic genes to other organisms, and that they cannot sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 89 publications
(110 reference statements)
1
32
0
Order By: Relevance
“…In this context, several strategies have been reported to construct UAA-dependent synthetic auxotrophs with low escape frequencies 19 , 20 , 39 43 . Despite exciting progress, simple and general strategies to efficiently construct UAA-dependent common bacterial strains with very low escape frequency remain to be an outstanding challenge 42 , 44 , 45 . And the utility of UAA-dependent synthetic auxotrophs in living animals is almost unknown.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, several strategies have been reported to construct UAA-dependent synthetic auxotrophs with low escape frequencies 19 , 20 , 39 43 . Despite exciting progress, simple and general strategies to efficiently construct UAA-dependent common bacterial strains with very low escape frequency remain to be an outstanding challenge 42 , 44 , 45 . And the utility of UAA-dependent synthetic auxotrophs in living animals is almost unknown.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that auxotrophy, created by eliminating essential genes, is effective for biological containment 11,12 . Nevertheless, it is possible that the containment system could be breached if HGT from natural microorganisms led to the acquisition of the essential genes 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Many forms of biological containment have been devised for uncontrolled environments that do not require human monitoring or input 11,12 . There are four main strategies for accomplishing biological containment: auxotrophy, kill switch, xenobiology, and physical containment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, escape from crops to adjacent ecosystems has a high potential, although persistence may be negligible. Mitigating effects caused by the escape of biostimulant microbes is an area of active research (Jack et al, 2020;Kim & Lee, 2020;Stirling & Silver, 2020;Ke et al, 2021), but the likelihood and frequency that PGPR escape occurs is uncertain.…”
Section: Boxmentioning
confidence: 99%